Analisa Daya Output Panel Surya Monokristalin 240 WP Pada Mesin Pengupas Kulit Singkong (Cut-All-Skin Cassava) - Agung Yesaya Rajagukguk; Ibrahim Lammada; Rahmat Hidayat (Peneliti.net, 2023)
Electrical energy is energy that is often used in everyday life. The absence of electrical energy will greatly disrupt the continuity of human activity. The potential for New, Renewable Energy (EBT) in Indonesia is very large but has not been utilized optimally because of the geographical gap between the location of energy sources and the location of energy demand and the initial investment costs are expensive. This research discusses the effect of solar radiation and surface temperature of solar panels on the output of solar panel electricity and the efficiency of monocrystalline solar panels with a capacity of 240 Watt Peak. The effect of solar radiation is directly proportional to the electricity generated. The highest radiation intensity occurred at 12:00 WIB 961 W/m2 capable of producing 187,63 Watts of power. Meanwhile, the lowest radiation intensity occurred at 07:00 WIB at 60,51 W/m2 and was able to produce a power of 41,7 Watts. The effect of the surface temperature of solar panels is directly proportional to the power generated every hour. The closer to the standard test temperature, which is 25oC, the greater the power generated. Most of the efficiency of solar panels is influenced by temperature, the lower the temperature and the closer to the standard test temperature of solar panels, which is 25oC, the higher the efficiency. Solar panel efficiency ranges from 0,09 – 0,46% with an average efficiency per three days of 0,19%.